Penggunaan Air Tanah Untuk Irigasi Di Kecamatan Widodaren Kabupaten Ngawi Tahun 2014 - Sarifah, Binti; , Ir. Imam Hardjono, M.Si (2016)
This research is conducted in Widodaren, District Ngawi. It aims to; (1) know about total water use for irrigation in Widodaren Sub-District, (2) how the use of ground water ? This research is using research methods by survey, (includes observation, measurement, and data recording in field) which based on mapping analysis. The research unit use farm land unit that it wasobtained from overlaying the landform map, slope map, soil map, and land use map. In research place, there are 601 artesian wells that dispersed in Widodaren which it was used by the peasants to irrigate the fields. It was dispersed in 12 villages, from these villages, the most consumers of the artesian wells are Sekalaras Village, SekarputihVilage, Banyubiru Village, and Kayudrejo Village.